Erratum to “Development and Validation of the Islamic Work Exemplary Scale in Indonesia” [Islamic Guidance and Counseling Journal 6(2) 2023] - Sumin Sumin; Heri Retnawati; Wajidi Sayadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
Refers to:Sumin, S., Retnawati, H., & Sayadi, W. (2023). Development and Validation of the Islamic Work Exemplary Scale in Indonesia. Islamic Guidance and Counseling Journal, 6(2). https://doi.org/10.25217/0020236392000Erratum:The authors requested a revision to the abstract in the original publication of this article. Specifically, at the behest of the corresponding author, the phrase